Three categories of similarities between the placenta and cancer that can aid cancer treatment: Cells, the microenvironment, and metabolites - Pang, Huiyuan; Lei, Di; Guo, Yuping; Yu, Ying; Liu, Tingting; Liu, Yujie; Chen, Tingting; Fan, Cuifang (Frontiers in Oncology, 2022)
Cancer causes the most deaths in the world and cannot be cured completely. The placenta and cancer share many similar processes; therefore, placental development can be seen as “pseudo-tumorigenesis”. These shared processes may offer ideas for treating cancer. Other factors include the shared processes of the decidua and tumor microenvironment (TME) and metabolites shared between pregnancy and cachexia. Both placental and tumor development heavily depend on the microenvironment. The decidua is the microenvironment of the placenta, and placenta and decidua inconsistencies can lead to placental diseases. Comparing the decidua with the TME and identifying key molecules that lead to placental disease may reveal new treatment targets for tumors. In addition, both the development of tumors and pregnancy can lead to alterations in systemic metabolism. Though both states feature increased energy consumption, the changes in metabolism in the two lead to opposite results. Therefore, an understanding of the altered metabolomics during pregnancy may reveal strategies to reverse cachexia and promote the survival of patients with tumors. Pregnancy may offer clues to cure cancer related to three categories: shared process of the placenta and cancer; shared features of the decidua and TME; and shared metabolism changes during pregnancy and cachexia.